Competitividad y gobernanza en el Estado Moderno: la práctica cortesana de Fernando II - Germán Gamero Igea (Les Cahiers de Framespa)
The royal entourage of Ferdinand the second of Aragon (known as the "Catholic King") can be studied as a space not only for competition but also for competitiveness. The king of Aragón faced a political situation, both in his own kingdoms and in Castile, that encouraged this situation in order to promote the stability of their governments. Furthermore, competition was a key solution to achieve the cooperation of the ruling elites, who were not always adept of his persona. To underestand better this extraordinary political context we will analyze three diferent items. First of all, the connection and competition between the king and the nobles outside the court. Secondly we will consider the competition inside the royal entourage. Finaly we will try to show how this competition even penetred in the military relationship between Ferdinand the Catholic and his servants. Cronicles will be used as main historical sources of this analisis but the paper will also consider archival references when necessary.